O sistema nacional de avaliação da educação superior e a gestão estratégica das instituições particulares de ensino superior: um estudo de casos múltiplos - Soares, José Antonio (2007)
The present research aims to discuss the role of the strategic management in the Undergraduate Private Institutions (IPES) before the insertion of the National System of Undergraduate Evaluation - SINAES. The central hypothesis of this dissertation is while the Government Program has promoted the mechanisms of controls and evaluations to improve the quality of undergraduate education in Brazil, IPES have adapted over the regulations by inserting of strategic management tools. At the same time these institutions have been trying to preserve the quality of education and the external competitiveness in a very aggressive market. The results of the collected information make this question clearly stated. The University and the associate and isolated colleges have posed a important role for the strategic management, before the implementation of SINAES. The other perspective of this research is the use of elements of the strategic management by IPES in the environmental competition (of excessive supplying sources) with a low level income Brazilian population scenario. Finally, it concludes that strategic management has been a vital element for IPES positive results.